PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI MIPA 1 SMA TAMAN RAMA - I Made Surat; I Wayan Muliana; I Komang Sukendra (LP3M Universitas PGRI Mahadewa Indonesia, 2022)
The Student Teams Achievement Division is one of the simplest cooperative learning methods, and is the best model to start with for teachers who use a cooperative approach. This type of research is classroom action research. The aim of this research is to find out the improvement of students' mathematics learning outcomes in trigonometry by applying the Student Teams Achievement Division type of cooperative learning model. The research subjects were students of class XI MIPA 1 SMA Taman Rama Denpasar in the academic year 2021/2022. The object of the research is the application of the Student Teams Achievement Division type of cooperative learning model and the students' mathematics learning outcomes. In this study through four stages of the activity process which includes (1) planning, (2) action, (3) observation, and (4) evaluation and reflection. Data collection techniques using test and observation methods. The results showed that the application of the Student Teams Achievement Division learning model could improve the mathematics learning outcomes of students in class XI MIPA 1 SMA Taman Rama Denpasar in the 2021/2022 academic year.